A qualidade de vida do trabalhador noturno e as relações do sono e do dia de descanso com o seu desempenho profissional - Zanardo, Marilza Delpino (2010)
This study refers to the Quality of Life of the Night Shift Workers and the relationships between the sleep, the Day of rest and their Professional Performance, which was guided by the objective: to investigate whether the change in the circadian rhythm (sleeping during the day and working at night) prevents the protective factors of labor activity from fulfilling their function. In order to collect the data, the following resources were used: socio-demographic and working conditions questionnaire; questionnaire on sleep conditions of the workers; questionnaire on the day of rest; range of quality of life (WHOQOL-Bref) and Index of Work Ability (IWA). The sociodemographic profile of the participants was, in its majority, characterized by male young adults (20 to 39 years old), married, with education equivalent to high school, most of them have children, who have been working at night for up to 8 years, the day of rest /leisure is not Saturday nor Sunday, they tend to sleep around 5, 8 and after 8 o’clock, they wake up around 1 p.m. and 5 p.m., with up to 6 hours of sleep. The perceive their Quality of Life as being good, as well as their health, they have a minimal differentiation between the four domains of QOL, where the psychological domain had a slight advantage among the others, the Index of Work Ability is good, with a correlation between the quality of life and work ability, the best IWA was the one presented by those who sleep earlier, wake up after 5 p.m. and have more than nine hours of sleep. There is no difference between the genders in terms of IWA and QOL, the single ones with children have the IWA category better than the married ones with children, but the married ones with children present a better QOL than the single ones with children. From correlations and organization by the similarities, 3 groups were formed: core 1, “Where is me?”, formed by workers 84 male (40 to 49 years) married, that lived with family which constituted with high school and worked at night for a period greater than 8 years; core 2 “Declining ones” formed by 39 young adults (30 to 39 years), married, that lived with the families that formed. Had minor children (up to 9 years). With high school and worked at night for a period of between three and eight years and core 3: “I do not care … I m Cool-headed”, formed by 72 young people (20-29 years), unmarried, still lived with their parents. With school, and were working at night only two years ago. The issue imposed by society that the more you work, the better you are, in general, makes people prioritize their career rather than many aspects, such as family, social activities, health and leisure. We face as essential need the advance towards a broader understanding of the leisure, considering its relations with the world of work